Nutritional status and dental caries of schoolchildren from Sobral - Ceará - AGUIAR,Bianca Dutra (2019)
ABSTRACT Objective: To examine the relationship between nutritional status and dental caries of schoolchildren from Sobral, Ceará, Braszil. Methods: Dental health and nutritional status of 92 children studying in two different schools and aging 5 years old were evaluated. The nutritional status was evaluated using the Body Mass Index (BMI), and the dental health status was evaluated using the Decayed, Missing, and Filling Tooth Index (DMFT-index). An interview with the parents of the children was also performed to investigate the socioeconomic profile and nutritional habits of the children. Results: A DMFT-index of 1.97 was found, and 39.6% of the childrenpresented overweight. Higher prevalence of dental caries was associated with low income, public schools, and less schooled parents. The variable overweight presented the inverse situation found for dental caries. Moreover, it was observed lower prevalence of caries in overweight children. Conclusion: Dental caries and nutritional status exhibited different behaviors in the population studied, which were driven by the sociodemographic profile of the family.